Polymer Nanocomposites Based on Nano Alumina - Chapa, Christian (Wiley, 2024)
Polymer nanocomposites based on nano-alumina (nAl 2 O 3 ) have emerged as a promising class of materials with a wide range of potential applications due to their unique combination of properties. This chapter provides a comprehensive overview of these materials, starting with the properties and applications of bulk alumina and nAl 2 O 3 . Different methods for obtaining nAl 2 O 3 nanoparticles are discussed, highlighting their physicochemical characteristics. The chapter then explores various preparation techniques for polymer nanocomposites with nAl 2 O 3 , detailing their preparation methods and physicochemical properties. Finally, the chapter explores the diverse potential applications of these nanocomposites, spanning from structural materials and drug delivery systems to environmental remediation and biomedical applications. The chapter concludes by highlighting the future prospects of polymer nanocomposites based on nAl 2 O 3 , emphasizing their potential to revolutionize various industries through their exceptional properties and diverse functionalities.